Agriculture and Allied Programmes and Co-Operation and Community Development Annual Plan Proposals 1968-69 Government of Kerala - Planning Commission (Planning Commission, 1968)
The State’s annual plan proposals for 1968-69 have been drawn up taking into account the suggestions received from the Planning Commission in its letters No. PC (P) 2167 dated 23-9-1967 and No. 14-2 (2) 67| Agri. dated 29-9-1967. The aggregate total outlay proposed for 1968-69 in the state sector of the plan comes to Rs. 65.43 crores. The capital outlay is estimated at Rs. 47.65 crores and the balance of Rs. 17.78 crores would be the revenue outlay. The foreign exchange requirement for 1968-69 comes to Rs. 5.95 crores of which Rs. 4.25 crores is for power schemes.
Planning Department